Accountability and Transparency in the Public Sector : The New Zealand Experience - Cangiano, M. (IMF Working Papers; Working Paper ;, 1996)
This paper describes the reforms introduced in the New Zealand public sector since the mid-1980s. The reforms included corporatization and privatization of most state-owned enterprises, the shift from a cash-basis to an accrual-basis accounting system and the compilation of a balance sheet for the central government and its entities, performance-based arrangements for the delivery of core government outputs; and institutional changes in expenditure control mechanisms. The paper also summarizes the impact of the reforms on government revenue and spending patterns, and discusses lessons learned from New Zealand's experience.